FORMS AND FUNCTIONS OF THE DYSPHEMISM USED BY THE STUDENTS OF SUPM LADONG, GREAT ACEH DISTRICT: BENTUK DAN FUNGSI PEMAKAIAN DISFEMISME SISWA SUPM LADONG ACEH BESAR - Wahab Fuadi; Mohd Harun; Razali Razali; Ramli Ramli (Jurnal Kata, 2022)
The purpose of the study is to describe (1) the forms of dysphemism in Ladong SUPM Students, Aceh Besar District, and (2) the function of dysphemism in Ladong SUPM Students, Aceh Besar District. Dysphemism is an expression that usually has a negative connotation, spoken as a form of expression of the psychological state that a person feels. This research was conducted by using qualitative approach. The data of this research were conversations that occur among SUPM Ladong Students, Aceh Besar District. Data processing was carried out in several stages, namely describing the form of the data, and the function of dysphemism used by the students of SUPM Ladong, Aceh Besar District when gathering and doing activities, then the data was transcribed and analysed. Data analysis was carried out in several stages - the interpretation of the forms of dysphemism and the interpretation of the function of the use of dysphemism. The results of the study revealed dysphemism language as follows: (1) the forms of dysphemism language in Ladong SUPM Students, Aceh Besar Regency consisted of monomorphemic, polymorphemic, phrases and sentences, and (2) the function of dysphemism language in Ladong SUPM Students, Aceh Besar District is to insult, express resentment, disclose threats, jokes, and damage or disturb.